Exploring the Impact of AI Technology Addiction on Stress, Anxiety, and Depression in Adolescents - Cindy Claudia Br Nadeak; Nurjasni Nurjasni; Helda Handayani Hia; Nurhikmah Siagian; Jesika Pionauli Sitorus; Atika Anjani; Syamsul Bahri (Pusat riset dan Inovasi Nasional, 2025)
The rapid development of Artificial Intelligence (AI) has made it a part of the teens' routine, but the intensity of its use raises concerns about mental health. This study aims to analyze the pattern of AI utilization and its impact on stress, anxiety, and depression in students of St. Petrus Medan High School using the framework of Self-Determination Theory (SDT), namely competence, autonomy, and connectedness). The research was conducted with a quantitative approach through a survey of 64 students using a total sampling technique, equipped with focused group discussions (FGDs) and literature review. The results show that more than 70% of students use AI on a regular basis, mainly through chatbots (81%) and social media (73%). Some students (35.9%) also use AI as a means of venting. Although 85.9% of respondents found AI to be helpful, the majority (59.3%) reported feeling inferior as a result of comparing themselves to AI results. These findings reveal a psychological paradox, where AI is perceived as a solution as well as a source of pressure. This condition has the potential to trigger stress and anxiety, although depressive symptoms do not yet appear to be dominant. This research emphasizes the importance of healthy digital literacy as well as mentoring from schools and parents to reduce the risk of AI addiction and maintain adolescent mental well-being.